Identifying the Economic Criteria for Sustainable Development Reporting Based on Islamic Texts at the Level of Companies - Morteza Yousefi; Rasoul Baradaran Hassanzadeh; Ali Reza Radbin; Mohammad Ali Rabbipoor; Saeed Hassanzadeh Delgsha (تحقیقات مالی اسلامی (پیوسته))
Creating a long-term economic advantage for companies can not meet the expectations of all stakeholders. Therefore, companies have no choice but to move towards sustainable development (Equitable distribution of development opportunities by considering the long-term time horizon and respecting intergenerational and intragenerational justice and various economic, social, environmental and business ethics aspects) in order to gain more legitimacy and meet the demands of all stakeholders. From the point of view of Islamic teachings, as long as a balanced human culture does not rule a society, we can not expect development from it.One of the main pillars and components of this development and culture is a balanced economy. The purpose of this study is to identify the components of the economic dimension of sustainability reporting in Islamic texts.To identify the components of the economic dimension of sustainability, qualitative content analysis with a semiotic approach was used. The Holy Quran and 148 volumes of authentic Shiite religious books (Among them are Nahj‌ ol Balagha, osul Kafi and Man La Yahzaraho al Faqih) were selected by non-probabilistic sampling method by purposeful sampling method of reaching the identifier with the sub-branch of sampling from known or famous cases as a sample. Findings showed that the components of the economic dimension of sustainability reporting in Islamic texts include 18 components and 268 examples. which can be effective for standardization in the field of sustainable reporting and disclosure regulations of the stock exchange and securites organization teachings and Islamic values.